2004
DOI: 10.1038/modpathol.3800036
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal myxoid chondrosarcomas do not show a chondrocytic phenotype

Abstract: Extraskeletal myxoid chondrosarcoma is a rare mesenchymal soft-tissue malignancy of putative chondrocytic differentiation. Occasional overt cartilage formation, positivity for S-100 protein, and ultrastructural analysis have supported this view. However, most extraskeletal myxoid chondrosarcomas do not show chondroid tissue formation, and S-100 protein is found much less commonly than has been reported. Both these observations cast doubt on the histogenetic classification of extraskeletal myxoid chondrosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 44 publications
(68 reference statements)
3
34
0
1
Order By: Relevance
“…A male predominance is reported. Despite the name, there is no convincing evidence of cartilaginous differentiation in most EMCS [96].…”
Section: Emcsmentioning
confidence: 99%
“…A male predominance is reported. Despite the name, there is no convincing evidence of cartilaginous differentiation in most EMCS [96].…”
Section: Emcsmentioning
confidence: 99%
“…In the present study, the canine tumor demonstrated all these histological features of EMC and did not involve any joints or bones, indicating it had an extraskeletal origin. The myxoid stroma seen in the present case was composed of acid mucopolysaccharides without hyaluronic acid, similar to that of human EMC 1,3,4,8,10) .…”
Section: Discussionmentioning
confidence: 61%
“…In the present case, type II collagen, known to be specific to cartilaginous tissues, was detected by immunostaining. This indicates that the present tumor had the potential to produce cartilaginous matrix, as observed in human EMC 1,8) . In addition, the ultrastructural findings of the tumor cells and their positive immunoreactivity to S-100a and vimentin suggest that the present tumor possessed some characteristics normally associated with chondroblasts 6,10) .…”
Section: Discussionmentioning
confidence: 74%
“…63 IDH1 and IDH2 point mutations are absent in MCS. 53,64 EXTRASKELETAL MYXOID CHONDROSARCOMA Although definite mature cartilage differentiation is not observed in extraskeletal myxoid chondrosarcoma (EMC), 43,44 it is included here given that the myxoid matrix histologically and histochemically resembles cartilage and EMC is often included as a cartilaginous tumor based on historical assertions.…”
Section: Genetic Featuresmentioning
confidence: 98%
“…Although extraskeletal myxoid chondrosarcoma histologically resembles cartilage, definite mature cartilage differentiation is not seen ultrastructurally or biochemically 43,44 Most common in deep soft tissue of proximal extremities compared with STC, which affects hands and …”
Section: Extraskeletal Myxoid Chondrosarcomamentioning
confidence: 98%